2020
DOI: 10.1109/jeds.2020.3008388
|View full text |Cite
|
Sign up to set email alerts
|

Channel Length Optimization for Planar LDMOS Field-Effect Transistors for Low-Voltage Power Applications

Abstract: We identify an optimum channel length for planar Laterally Diffused Metal-Oxide-Semiconductor (LDMOS) field-effect transistors, in terms of the specific on-resistance, through systematic device simulation and optimization. We simulate LDMOS devices with different channel lengths ranging from 100 nm to 10 nm, modifying the length of the drift region and doping concentration of the body region to match a predetermined leakage current suitable for lowvoltage power applications (3.3V and 5V). For devices with a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Thus, it is shown that the variations in conduction characteristics are caused mainly by the number of GB located in the channel 3 . The V th is defined by the constant-current method, which determines the V th as the V g value for I d = 10 − 7 A/µm 15 .
Figure 3 Electron potential energy of the proposed devices with and without GB at a read operation.
…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is shown that the variations in conduction characteristics are caused mainly by the number of GB located in the channel 3 . The V th is defined by the constant-current method, which determines the V th as the V g value for I d = 10 − 7 A/µm 15 .
Figure 3 Electron potential energy of the proposed devices with and without GB at a read operation.
…”
Section: Resultsmentioning
confidence: 99%
“…The V th values were extracted using the constant-current method at 100 nA μm −1 . [27][28][29] Figure 3 presents the transfer curves of the 200 JL bulk-FinFET-based 1T-DRAM samples fabricated using the TiN, MoN, TaN and WN gate materials. Note that each metal material consists of two or more grains and each grain has a different WF value depending on the grain orientation.…”
Section: Device Structure and Simulation Methodsmentioning
confidence: 99%
“…For the TaN metal gate, all the V th values could not be extracted because all drain currents in the I ds -V gs curves were greater than 100 nA μm −1 , which was a reference value. [27][28][29] The standard deviations (SDs) for the V th values were 14.8 mV, 46.0 mV and 46.0 mV, respectively. The relative standard deviations (RSDs) were 5.43%, 8.83% and 12.6%, respectively.…”
Section: Device Structure and Simulation Methodsmentioning
confidence: 99%
“…Laterally-Diffused Metal-Oxide-Semiconductor (LDMOS) field-effect transistors are commonly used in lowvoltage [1], [2], mid-voltage [3], [4], and high-voltage [5]- [8] applications because of their promising performance and their use of silicon technology. Ever growing commercial applications of LDMOS transistors has attracted much attention in the research community [9]- [11].…”
Section: Introductionmentioning
confidence: 99%